An Analysis of the Obstacles in Implementing Differentiated Learning in the Merdeka Curriculum at SD Negeri 02 Tiumang - Darniyanti, Yulia; Nanda, Dodi Widia; Husnah, Deati Nadiatul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to describe the inhibiting factors in the implementation of differentiated learning at SD Negeri 02 Tiumang. In the Independent Curriculum, there is a differentiated learning approach which provides freedom for teachers to adjust learning to the needs of students. However, in its implementation, there are quite a few obstacles that arise in the field. The method used in this study is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Data analysis techniques use data reduction techniques, data presentation and drawing conclusions. The validity of the data is tested by triangulation techniques and using reference materials. Based on the results of the study, the researcher can conclude that there are several inhibiting factors in the implementation of differentiated learning, including: lack of teacher understanding of the independent curriculum itself, both in terms of structure and planning of learning devices, difficulties in implementing differentiated learning in the learning process, obstacles in implementing differentiated learning, limited facilities and infrastructure, stuttering in using technology, lack of supporting media in the learning process in the classroom, time constraints, and difficulty in finding creative idea references. These findings indicate that the implementation of differentiated learning still faces obstacles that require attention and strategic solutions so that differentiated learning can be achieved optimally.